Kampung Warna-warni Jodipan Evaluasi Visual Lanskap Pada Kampung Warna-Warni Jodipan Kota Malang: Visual Lanskap - Hawo Rato, Muhammad Nova Fazril Fauzi; Soelistyari, Hesti Triana; Alfian, Rizki (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2024)
The colorful village of Jodipan in Malang City, East Java is a residential village in the city center. Kampung Warna-Warni is a slum settlement that has a higher population and building density. In 2017, a group of Public Relations students from the University of Muhammadiyah Malang (UMM) initiated changes that succeeded in turning the Jodipan settlement, which originally looked shabby, into a beautiful and elegant area with colorful paint in the village. In this research, the method was obtained from survey results and documentation. In assessing the visual quality of the Jodipan Colorful Village landscape using the Scenic Beauty Estimation (SBE) method. The recommendations produced in this research are in the form of recommendations for illustrative images such as adding landscape-forming elements (hardscape and softscape). Keyword: Kampung Warna-Warni Jodipan,Visual Lanskap, SBE